Green synthesis of silver nanoparticles using acacia lignin, their cytotoxicity, catalytic, metal ion sensing capability and antibacterial activity. Issue 5 (October 2019) - Aadil, Keshaw R.; Pandey, Neha; Mussatto, Solange I.; Jha, Harit
Graphical abstract: Highlights: Single step method for the synthesis of silver nanoparticles was developed. Cytotoxicity of Acacia lignin and AGNP on MCF-7 cancer cell line was studied. Study reported the ultra-sensitivity detection ability of AGNPs towards heavy metal ions. The lignin-silver nano catalyst showed excellent catalytic activity in the degradation of MB and p -NP. AGNPs displayed antimicrobial properties against gram positive and gram negative microorganism. Abstract: The present study uncovers the in-vitro cytotoxicity, sensing properties, catalytic and antibacterial activity of lignin functionalized silver nanoparticles (AGNPs). Fabricated AGNPs were characterized using UV–vis spectroscopy, particle size, X-ray diffraction (XRD) and Transmission Electron Microscopic (TEM) analyses. The typical surface plasmon resonance peak of AGNP was recorded at 410 nm, as confirmed from UV–vis spectrum. Synthesized AGNPs displayed spherical shape and face centric cubic structure with average size of 10–50 nm. In-vitro cytotoxicity assay using MCF-7 cancer cell line revealed that the extracted lignin was non-toxic while AGNPs displayed toxicity at both 5 and 50 μg/ml concentrations, respectively. Evaluation of the sensing property of AGNPs suggested that the lignin stabilized silver nanoparticles have potential to detect the concentration of heavy metal ions up to nanomolar range. AGNPs also showed good catalytic activity with the rate constants of 0.00098 and 0.01525 min −1 respectively for methylene blue dye and p -nitrophenol reduction. Moreover, AGNPs displayed antibacterial efficacy against both gram positive and negative strains. These findings suggest that lignin mediated AGNPs can find applications in different fields including biomedical, drug delivery, textile, biosensor, food packaging material, and textiles.